A comparative study on the combination of life cycle assessment and ecological footprints: solar photovoltaic power generation vs. coal power generation in Ningxia - Luo, Jinni; Yang, Hexu; Zhang, Liangxia; Liu, He; Wang, Yidan; Hao, Chen (Frontiers in Energy Research, 2024)
In China, where energy activities, predominantly driven by fossil fuel combustion, account for nearly 90% of the country’s greenhouse gas (GHG) emissions and coal power alone contributes over 40%, the shift towards carbon neutrality is a critical national ambition. This study conducts a comprehensive comparison of the environmental impacts of solar photovoltaic power generation (SPPG) and coal power, employing both life cycle assessment and ecological footprint analysis. We meticulously analyze the complete lifecycle of SPPG, pinpointing key stages of GHG emissions, and offer nuanced, localized policy recommendations. Our findings indicate that a 1 kWp SPPG module emits 1,601.18 kg of GHGs over its lifespan, equating to 1.35 kg/kW·h per unit of electricity produced—substantially lower than the 4.81 kg/kW·h emitted by coal power, thus highlighting the latter’s heightened environmental detriment. Additionally, this study assesses the ecological footprint of both energy sources in Ningxia. SPPG emerges with an ecological surplus, showcasing a per capita footprint of 0.0342 hm2, compatible with Ningxia’s ecological capacity. In stark contrast, coal power exhibits a sustained ecological deficit over the past 5 years, with a growing per capita footprint of 0.6529 hm2, underscoring its unsustainability. This research provides a detailed comparative analysis of the environmental impacts of SPPG and coal power in Ningxia, offering valuable insights for energy policymakers and industry stakeholders. It underscores the urgent need for industrial restructuring towards more sustainable and renewable energy sources, aligning with China’s broader objectives of environmental preservation and achieving carbon neutrality.